2015
DOI: 10.2196/resprot.4864
|View full text |Cite
|
Sign up to set email alerts
|

Twitter-Delivered Behavioral Weight-Loss Interventions: A Pilot Series

Abstract: BackgroundLifestyle interventions are efficacious at reducing risk for diabetes and cardiovascular disease but have not had a significant public health impact given high cost and patient and provider burden.ObjectiveOnline social networks may reduce the burden of lifestyle interventions to the extent that they displace in-person visits and may enhance opportunities for social support for weight loss.MethodsWe conducted an iterative series of pilot studies to evaluate the feasibility and acceptability of using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 32 publications
2
85
0
Order By: Relevance
“…Two recent systematic reviews indicated that online social networks have been primarily used as an adjunct to in-person or web-based weight loss interventions, rather than as the primary treatment modality [18,19]. We recently conducted a series of pilot studies that demonstrated that delivering a weight loss intervention via a private Twitter group is feasible and acceptable [34]. Our results suggest that women of childbearing age are interested in a weight loss program delivered entirely via Twitter.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Two recent systematic reviews indicated that online social networks have been primarily used as an adjunct to in-person or web-based weight loss interventions, rather than as the primary treatment modality [18,19]. We recently conducted a series of pilot studies that demonstrated that delivering a weight loss intervention via a private Twitter group is feasible and acceptable [34]. Our results suggest that women of childbearing age are interested in a weight loss program delivered entirely via Twitter.…”
Section: Discussionmentioning
confidence: 80%
“…Future studies could include asking women to evaluate how engaging they would find specific posts or articles, and also examining which types of posts netted the most engagement. In our previous study of a Twitter-delivered weight loss intervention, participants reported that one of the biggest barriers to engaging was not being sure what to post [34], suggesting that providing participants with guidance on what to post may be one avenue for enhancing engagement. Research is needed to understand how to increase engagement in behavioral interventions delivered via online social networks, including how to encourage visible interactions from participants who prefer to lurk (i.e., read content without visibly engaging) [42].…”
Section: Original Researchmentioning
confidence: 99%
“…[3] In fact, large patient communities have organically developed online which may provide a critical mass for health promotion interventions. [4,5] For example, online social networks are increasingly being researched as a modality for delivering behavioral weight loss interventions. [6] Some studies have used online social networks as an adjunct to clinic-based weight loss programs, either by conducting scheduled group chats online [7,8] or by providing a message board/forum for participants to submit questions and chat.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Other studies have used online social networks as the main delivery modality for weight loss interventions. [5,11,12] Two systematic reviews of 12 and 20 studies, respectively, revealed that such interventions have shown modest outcomes. [6,13] Only one study isolated the impact of the online social network, showing that an online exercise intervention that included an online social network outperformed the same intervention without the online social network.…”
Section: Introductionmentioning
confidence: 99%
“…A third approach has been to incentivize participants based on the number of posts they contributed to the Facebook group [51]. Finally, some recent studies have investigated the type of intervention content that stimulates the highest level of engagement [27,[52][53][54][55]. One study found that polls, posts asking participants to suggest a tip for others, and weight-related posts were the most engaging among participants in a 4-month weight loss study [52].…”
Section: Discussionmentioning
confidence: 99%